2004
DOI: 10.1042/bj20040522
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the first non-insect invertebrate functional angiotensin-converting enzyme (ACE): leech TtACE resembles the N-domain of mammalian ACE

Abstract: Angiotensin-converting enzyme (ACE) is a zinc metallopeptidase that plays a major role in blood homoeostasis and reproduction in mammals. In vertebrates, both transmembrane and soluble ACE, containing one or two homologous active sites, have been characterized. So far, several ACEs from invertebrates have been cloned, but only in insects. They are soluble and display a single active site. Using biochemical procedures, an ACE-like activity was detected in our model, the leech, Theromyzon tessulatum. Annelida is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…Indeed, drosophila ACEs intercalate between them, and Cg ACE appears close to the bacterial Xc ACE, whereas Tt ACE clusters with vertebrate isoforms. Because both leeches and oysters belong to the Lophotrochozoa, such an observation might reflect complex evolutionary relationships between annelids and molluscs, and may also involve the specific parasitic trait of leeches, as discussed elsewhere [30]. Besides, the finding of a unique catalytic region within Cg ACE, and more generally within all lophotrochozoan ACE-like enzymes described to date [30], seems consistent with the late occurrence of genome duplication during the course of animal evolution.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Indeed, drosophila ACEs intercalate between them, and Cg ACE appears close to the bacterial Xc ACE, whereas Tt ACE clusters with vertebrate isoforms. Because both leeches and oysters belong to the Lophotrochozoa, such an observation might reflect complex evolutionary relationships between annelids and molluscs, and may also involve the specific parasitic trait of leeches, as discussed elsewhere [30]. Besides, the finding of a unique catalytic region within Cg ACE, and more generally within all lophotrochozoan ACE-like enzymes described to date [30], seems consistent with the late occurrence of genome duplication during the course of animal evolution.…”
Section: Discussionsupporting
confidence: 55%
“…Because both leeches and oysters belong to the Lophotrochozoa, such an observation might reflect complex evolutionary relationships between annelids and molluscs, and may also involve the specific parasitic trait of leeches, as discussed elsewhere [30]. Besides, the finding of a unique catalytic region within Cg ACE, and more generally within all lophotrochozoan ACE-like enzymes described to date [30], seems consistent with the late occurrence of genome duplication during the course of animal evolution. Indeed, this duplication occurred far after the Protostomes-Deuterostomes divergence and is widely admitted to explain the presence of two active site ACE-coding sequences in vertebrate genomes, such as the human ace-1 gene [3].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Although the precise function of ACE in this location is not fully understood, the nonspecificity of ACE peptide cleavage suggests the hypothesis that it may play a role in the digestion of peptides (Rivière et al, 2004). Analysis has demonstrated that single-catalytic domain ACE-like enzymes are expressed in the gut of other species such as the moth (Spodoptera littoralis: ABW34729.1) or the leech (Theromyzon tessulatum: AAS57725.1) (Wijffels et al, 1996;Rivière et al, 2004;Lemeire et al, 2008). In the leech, the expression of ACE is restricted to intestinal epithelial cells.…”
Section: Digestionmentioning
confidence: 99%
“…that Race is expressed in the embryonic, larval and pupal stages of D. melanogaster, as analyzed by Northern blotting. Also for the non-insect invertebrate T. tessulatum (leech), TtACE was present throughout the life cycle (Riviere et al, 2004). Fig.…”
Section: Article In Pressmentioning
confidence: 98%